Pasture growth model to assist management on dairy farms: Testing the concept with farmers. (21st February 2013) - Romera, Alvaro; Beukes, Pierre; Clark, Dave; Clark, Cameron; Tait, Andrew
Abstract: A prototype software tool (Pasture Growth Simulation Using Smalltalk, PGSUS) was developed to estimate herbage mass at an individual paddock level so that farmers can measure herbage mass less frequently. PGSUS was tested on 10 commercial and two research dairy farms in New Zealand. Herbage mass estimations from PGSUS were accurate, with an average residual standard deviation of 252 kg dry matter ha −1 across all farms. When interviewed, all farmers gave high ratings to PGSUS, except for the amount of data collection required, and user friendliness, which were given a medium ranking. The extra time dedicated to PGSUS by farmers was 43 min per week on average, which was judged acceptable by farmers. However, in practice, the participating farmers were unable to enter all the information required for the system to work as intended. It is concluded that while it is technically possible to use a pasture model to estimate herbage mass at paddock level with sufficient accuracy to aid decision making, the recording of grazing events proved to be a major obstacle. If the issue of data entry can be overcome, it is envisaged that a full commercial version of PGSUS should appeal to objective‐data‐oriented farmers, most probably as an add‐on to existing commercial farm software.